Peningkatan Perilaku Peduli Lingkungan Melalui Pembinaan Dan Pengembangan Usaha Kesehatan Sekolah (UKS) Di SMAN 1 Pasaman - Hawariyun M.Si (STKIP Pesisir Selatan, 2016)
AbstrakBased on the observations that have been researchers did students at SMA Negeri 1 Pasaman, it was found that the ability gurudan students in preparing Environmental Care Behavioral improvement programs is still low. The purpose of this study is to describe and obtain information about the efforts of teachers and students Improved capabilities in developing improvement programs through the Creation and Development of School Health Unit (UKS) Students of SMA Negeri 1 Pasaman. This research is a school action. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 30 students in the building by 8 The Master SMA Negeri 1 Pasaman. Data were collected by using observation sheet. Data were analyzed using percentages. The results showed that Pembinssn and Development of School Health Unit (UKS) can enhance students' skills in improving behavior pedulilingkungan in SMA Negeri 1 Pasaman. , This is evidenced by the increase in the ability of the students in preparing environmental care behavior improvement program from the first cycle to the second cycle. The average ability of students and teachers in preparing a program to improve the behavior of environmental care in the first cycle is 52.2 with less category and the second cycle is 82 to either category.Keywords: Ability Student, Program Improvement in Environmental Care, UKS